Kontribusi Mazhab Teologis Mu'tazilah Dalam Perkembangan Sastra Arab Era Aabbasiyah Studi Analisis Kritis Historis - Zulhelmi Zulhelmi; Hajjah Rafidah binti Haji Abdullah; Shuhaida Hanim binti Mohamad Suhane; Ashwaq Ismail S Batubara; Ashwaq Ismail S Batubara; Delami (An-Nahdah Al-'Arabiyah)
This research aims to reveal the contributions of the Mu'tazilah school of thought to the development of Arabic literature during the Abbasid dynasty. This study is important to ensure that today's generation of Muslims does not deny the achievements of Mu'tazilah writers of the Abbasid era due to theological differences. The main issue addressed in this research is the various forms of Mu'tazilah's contributions to the development of Arabic literature during the Abbasid dynasty. The reason for focusing on the Abbasid period is that during this time, the Mu'tazilah held a special place in the royal court, with Caliph al-Ma'mun even making Mu'tazilah the official ideology of the kingdom. This research is qualitative in nature, with data collected through library research. The theoretical framework employed is historical criticism theory, as the study's object involves historical facts of the Islamic golden age. The researcher concludes that the Mu'tazilah made significant contributions to the development of Arabic literature. These contributions are evident in the emergence of prominent literary figures and critics such as al-Jahiz, Abu Hayyan al-Tawhidi, and al-Qadi al-Jurjani. Moreover, they also contributed to the creation of new literary genres, including al-Munadharah, al-Jadal, al-Mawa'id, and al-Adab al-Dini. In light of these contributions, it is hoped that Muslim scholars in the field of Arabic language and literature will acknowledge these historical achievements.